Diagnosis of liver fibrosis in ageing patients with HIV at risk for non-alcoholic fatty liver disease in Italy and Canada: assessment of a two-tier pathway. (March 2022) - Sebastiani, Giada; Milic, Jovana; Gioe, Claudia; Al Hinai, Al Shaima; Cervo, Adriana; Lebouche, Bertrand; Deschenes, Marc; Cascio, Antonio; Mazzola, Giovanni; Guaraldi, Giovanni
Abstract: Background: Since the introduction of effective antiretroviral therapy, liver-related mortality has increased ten-fold in ageing people with HIV. This trend is driven by ageing-related metabolic conditions that cause non-alcoholic fatty liver disease (NAFLD), which affects 35-65% of people with HIV. Clinically significant (stage 2–4) liver fibrosis develops in over 15% of people with HIV who have NAFLD. Strategies are needed to identify people with HIV at risk for significant liver fibrosis and reduce cirrhosis-related complications. Non-invasive tests to diagnose liver fibrosis include ultrasound-based transient elastography and serum biomarkers. Transient elastography is a feasible tool to assess liver fibrosis, but it is not largely accessible in HIV clinics. We aimed to determine whether a two-tier care pathway with assessment of simple serum biomarkers for fibrosis as first tier could reduce the need for the specialist transient elastography test (second tier). Methods: Patients were consecutively identified through a clinical programme for liver disease in people with HIV in Canada and Italy. We applied a two-tier care pathway to three prospective cohorts of people with HIV at risk for NAFLD, defined as those with elevated liver transaminases, body mass index (BMI) of 25 or greater, or diabetes. Patients with alcohol abuse or coinfection with hepatitis B or C viruses were excluded. Five simple serum biomarkers of fibrosis, based on liver transaminases, platelets, and BMI (fibrosis-4 index [FIB-4], BARD [BMI, AST to ALT ratio, diabetes] score, NAFLD fibrosis score, AST to ALT ratio, and AST-to-platelet ratio index [APRI]) were applied as a first-tier assessment to exclude significant liver fibrosis. All patients then received transient elastography. We assessed the decrease in referral for transient elastography that would have occurred based on biomarker assessment and discordance between high transient elastography (≥7·1 kPa), indicating significant liver fibrosis, and low serum fibrosis biomarkers (FIB-4 <1·3, BARD score 0–1, NAFLD fibrosis score less than –1·455, AST to ALT ratio <0·8, and APRI <0·5). We also assessed independent factors associated with that discordance by multivariable logistic regression analysis. Findings: We included 1202 people with HIV at risk for NAFLD (mean age 51·2 years [SD 10·1], 914 [76%] male and 288 [24%] female, mean HIV duration 16·3 years [SE 9·7], mean BMI 26·5 Kg/m 2 [SD 4·5]; prevalence of diabetes 49·5%). 222 (18·5%) of these participants had significant liver fibrosis according to transient elastography. Assessment of simple fibrosis biomarkers would have decreased transient elastography referrals between 22·5% (BARD score) and 82·4% (APRI). Discordance rate ranged from 3·9% (NAFLD fibrosis score) to 11·1% (APRI). After adjustment for age, sex, presence of diabetes, level of HDL cholesterol, and CD4 cell count, BMI (odds ratio 1·12, 95% CI 1·07–1·17) and triglyceride level (1·25, 1·08–1·46) were independent predictors of discordance for low APRI and high transient elastography. Interpretation: Use of a two-tier pathway to identify liver fibrosis in ageing people with HIV at risk for NAFLD could reduce transient elastography examinations by a substantial proportion, reducing costs and helping to optimise use of resources in HIV care. Funding: GS is supported by a Senior Salary Award from Fonds de recherche du Québec—Santé (number 296306).